Keterampilan Menulis Teks Narasi Siswa Kelas V Madrasah Ibtidaiyah Nurussalam Kembang Sri Tetebatu Sikur Lombok Timur - Busro; H. Sukri; Mansur Hakim; Heri Setiawan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Narrative text writing skills represent essential language competencies that primary school students must possess. However, observations conducted at Madrasah Ibtidaiyah Nurussalam Kembang Sri revealed that a portion of students still encounter difficulties in developing ideas, structuring story plots, and utilizing capital letters and punctuation in accordance with Indonesian language conventions. This study aims to describe the narrative text writing skills of fifth-grade students at Madrasah Ibtidaiyah Nurussalam Kembang Sri and to identify the factors influencing these skills. This study employed a mixed-methods approach with a sequential explanatory design. The research subjects consisted of 16 fifth-grade students and their homeroom teacher. Data were collected through narrative text writing tests, interviews, and documentation. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed using the Miles and Huberman model. The results demonstrated that the students' narrative text writing skills fell into the moderate category, with an average score of 55.8. The aspects of idea development (68.75%) and story plot (65.63%) were classified in the good category, whereas other aspects were in the moderate category. The lowest percentages were found in the use of capital letters (45.31%) and punctuation (43.75%). Factors influencing writing skills include internal factors, such as low learning motivation, reading interest, self-confidence, and a tendency to fatigue easily while writing, as well as external factors, including excessive gadget use and a lack of consistent writing habits. Consequently, students' narrative text writing skills still require improvement through enhanced motivation, reading interest, and more intensive writing instruction.